2023
DOI: 10.1080/14786419.2023.2287183
|View full text |Cite
|
Sign up to set email alerts
|

Lippia origanoides essential oil increases longevity and ameliorates β-amyloid peptide-induced toxicity in Caenorhabditis elegans

Ana Maria Henrique Moniz,
Francisco Humberto Xavier Junior,
Giovanna Melo Martins Silva
et al.

Abstract: Lippia origanoides essential oil (LOEO) is extensively utilized as food preservative due to its antioxidant and antibacterial activities. In this study, the antioxidant and anti-aging effects of LOEO was investigated in vivo using the nematode Caenorhabditis elegans. The gas chromatography-mass spectrometry analysis indicated that the main components of LOEO are carvacrol and thymol. LOEO treatment improved physiological parameters such as pharyngeal pumping, locomotion and body size indicating that is not tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In recent years, researchers have made good progress using these transgenic C. elegans models to conduct a number of AD-related studies. For example, Lippia origanoides essential oil (LOEO) ( Henrique Moniz et al, 2023 ), Hesperidin ( Kumar et al, 2023 ), A fruit extract of Styphnolobium japonicum (L.) ( Thabit et al, 2023 ) have also been found to be efficacious in the treatment of AD in nematode model-based studies. Overall, the practice of AD drug development using the C. elegans model has become more mature, providing a bright prospect for high-throughput screening of drugs for neurodegenerative diseases ( Paul et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have made good progress using these transgenic C. elegans models to conduct a number of AD-related studies. For example, Lippia origanoides essential oil (LOEO) ( Henrique Moniz et al, 2023 ), Hesperidin ( Kumar et al, 2023 ), A fruit extract of Styphnolobium japonicum (L.) ( Thabit et al, 2023 ) have also been found to be efficacious in the treatment of AD in nematode model-based studies. Overall, the practice of AD drug development using the C. elegans model has become more mature, providing a bright prospect for high-throughput screening of drugs for neurodegenerative diseases ( Paul et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The unique advantages of C. elegans have allowed its wide use in screening for natural compounds with potential anti-AD effects. For instance, studies based on this model have demonstrated the antioxidant and anti-aging properties of Lippia origanoides essential oil, and highlighted its potential for the prevention and treatment of AD ( Henrique Moniz et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%